The Relationship of Knowledge and Eating Patterns with The Incident of Hypertension in Pre-Elderly - Aysah, Feby; Bus Umar, Hermita; Yuniritha, Eva; Kasmiyetti; Sartika, Wiwi (proceedinginternational, 2024)
The incidence of hypertension is always increasing due to many factors. This study aims to determine the relationship between knowledge and diet with the incidence of hypertension in the elderly in Jorong Sikabu Hilir, Ulakan Tapakis District, Padang Pariaman Regency.This study used a cross-sectional design, the research sample was all pre-elderly people in Jorong Sikabu Hilir, Ulakan Tapakis District, Padang Pariaman Regency, totaling 42 people. Data collection uses the SQ-FFQ form and questionnaire. Data analysis using Chi Square with a confidence level of 95%. The results of the research found that 54.8% of respondents had hypertension, 52.4% had poor knowledge and 57.1% had poor eating patterns. Statistically there is a significant relationship (p=0,032) between knowledge and the incidence of hypertension, there is a significant relationship between diet (p=0,035) and the incidence of hypertension. It is hoped that the puskesmas will emphasize more on knowledge about the link between hypertension and cardiovascular disease and the community, especially the pre elderly population (45-54 years) will better maintain their diet and consume foods high in potassium and maintain an ideal body weight to prevent the occurrence of hypertension.